ECHOES OF EQUITY: COMMERCIAL JUSTICE IN THE WORLD OF SILAPPATHIKARAM - Dr. D. Ramaiyan; S. Rameshkumar; S. Maheswari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The ancient Tamil epic Silappathikaram, authored by Ilango Adigal, is a literary masterpiece that vividly portrays the socio-economic and cultural dynamics of the Sangam period. One of the most significant aspects of the epic is the depiction of Vanika Kutru the court of merchants where justice and commerce intersect. This research paper examines the concept of justice and commerce within the framework of Vanika Kutru, highlighting its pivotal role in maintaining ethical business practices and ensuring social harmony. Through a literary analysis of Silappathikaram, this study explores how Vanika Kutru functioned as a judicial body that not only resolved commercial disputes but also upheld moral and ethical standards in trade. The paper delves into the principles of justice embedded within the court’s proceedings and how they reflect the values of the ancient Tamil society. It also discusses the representation of merchant guilds as integral to community governance and social order. By analyzing the portrayal of Vanika Kutru and its judicial practices, this research paper seeks to provide a comprehensive understanding of the interrelationship between commerce and justice in ancient Tamil civilization. Furthermore, the study draws comparisons between the ancient system and contemporary commercial arbitration, highlighting the relevance of traditional practices in modern contexts.